Analysis Shift in the Translation of Childrens Story That Sunday Morning by Savita Singh - Afriani, Gabby Ratu; Marlianingsih, Noni (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
This study focuses on noun phrase translation alterations as well as noun phrase meaning translation. The goal of this research is to characterize the translation shifts of noun phrases used in the translation of That Sunday Morning, as well as to identify the meaning translation in noun phrases discovered while translating English noun phrases to Indonesian noun phrases in that Sunday Morning. This study method used was a comparative-descriptive-qualitative approach. The results obtained in this study are 80% (eighty percent) category shift, 12% (twelve percent) level shift, along with 4% (four percent) form-based translation and meaning-based translation. Catford (1965) proposed the notion of translation shift, which was then used to analyze data. Larson's (1984) theory of meaning based on translation was utilized. Quirk, Randolph, and Sidney Greenbaum (1973) offered a theory on English noun phrases. The results of this study are the translation of shifts of noun phrases and the translation of meanings in noun phrases. After collecting all the data, then put the data as examples. Examples of shifts in structure and basic meaning of translation (translation with regard to expressions).